2014
DOI: 10.1139/cjb-2013-0183
|View full text |Cite
|
Sign up to set email alerts
|

Perianth colour affects germination behaviour in wind-pollinated Salsola rubescens in Arabian deserts

Abstract: Salsola rubescens Franch. is a wind-pollinated halophytic shrub that produces fruits with red and yellow winged perianths. Germinability of seeds from both fruit types was determined under various light, temperature, and salinity treatments. Red seeds, with and without winged perianths, were heavier than yellow seeds. Germination percentage and germination rate index (speed) were significantly affected by the perianth colour, presence of wings, and temperature and light of incubation and most of their interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 31 publications
6
37
0
Order By: Relevance
“…We also found that removal of the perianth wing significantly increased germination percentage and rate in both colour morphs. These results are in a line with previous studies on seed germination in S. vermiculata ( and ), S. villosa (), and S. rubescens (). Under natural conditions, the wings do gradually decompose in the soil and there might also be leaching of the chemicals that inhibit seed germination.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that removal of the perianth wing significantly increased germination percentage and rate in both colour morphs. These results are in a line with previous studies on seed germination in S. vermiculata ( and ), S. villosa (), and S. rubescens (). Under natural conditions, the wings do gradually decompose in the soil and there might also be leaching of the chemicals that inhibit seed germination.…”
Section: Discussionsupporting
confidence: 93%
“…Several reproductive and ecological strategies are used by desert plants to survive under unpredictable climatic conditions (, , and ). Infrequent, variable seed germination and seedling establishment is one of the strategies adopted by desert species to survive extremes of high temperature, low rainfall and high salinity ().…”
mentioning
confidence: 99%
“…In order to enhance survival and fitness in such stressful environments, desert plants developed complementary sets of adaptation and survival strategies during different stages of their life cycles (Gutterman 2002;El-Keblawy 2004). For example, factors such as seed morphology, mass, wing size and persistence can all greatly affect the seed dispersal, dormancy and germination behavior of many desert plants (Xing et al 2013;El-Keblawy et al 2013;El-Keblawy & Bhatt 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Seed heterogeneity, which is the variations in size, colour and weight is a phenomena commonly reported in many species of the desert environment (Volis, & Bohrer, 2013;El-Keblawy, Bhatt, & Gairola, 2013). Heterogeneity in seeds mostly occurs due to physiological, environmental and genetic factors (Dickson, & Boettger, 1982;Atak et al, 2008).…”
mentioning
confidence: 99%
“…in addition, the study aimed to assess the impact of seed colour on light and temperature requirements during germination for the two species. We assume that colours of structures surrounding seeds and seed colours would affect light filtering properties, which in turn affect germination requirements, especially light of incubation (xing et al 2013, El-Keblawy, Bhatt, & Gairola, 2013. Germination behavior of the two species was assessed through studying final germination percentage and germination rate.…”
mentioning
confidence: 99%